1240 Obstructive Sleep Apnea Management in Weill-Marchesani Syndrome: A Case Report. (27th May 2020) - Monceaux, Brittany; Smalley, Megan; Okorie, Ugorji; Roberts, Edmond; Liendo, Cesar; Asghar, Sheila; Chernyshev, Oleg
Abstract: Introduction: Weill-Marchesani Syndrome (WMS) is a rare systemic genetic connective tissue disorder which usually presents with symptoms of short stature, limited joint movement, and eye problems such as glaucoma and microspherophakia. This genetic condition is associated with fibrous tissue hyperplasia. WMS is inherited as autosomal dominant or autosomal recessive patterns in families leading to a variability in presenting phenotype. Few papers have been written on airway management during anesthesia but as far as we know, this is the first case report on obstructive sleep apnea management in a patient with WMS. Report of Case: A 9 year old boy with a past medical history of Methylene THF Reductase deficiency, von Willebrand's Disease, seizure disorder, premature birth, developmental delays and Weill-Marchesani syndrome was referred to Sleep Medicine due to tonsillar hypertrophy (3+), snoring and witnessed apneas. Upon physical examination, patient had mid-facial hypoplasia, retropositioning of the mandible, high arched palate, Mallampti class IV, maxillary hypoplasia and mandibular hypoplasia. He had been evaluated by ENT which determined the patient to be too high risk due to his medical conditions for T&A. The patient had a polysomnogram in 2018 indicating OSA with an apnea-hypopnea index of 4.2 and a minimum oxygen saturation of 91%. After a CPAP titration study, the patient was started on Auto CPAP of 5-15 cmH2O and has shown improvement in symptoms based on subjective and objective compliance report. Patient has been able to tolerate PAP therapy well with 100% compliance greater than 4 hours per night. Conclusion: This case is the first illustrating OSA in a patient with Weill-Marchesani Syndrome. In WMS, the causes of OSA are not only due to tonsillar hypertrophy, but multifactorial, including craniofacial abnormalities. Given the high risk of surgical complications in WMS patients, PAP therapy appears to be a reasonable option for OSA management.